Co-creation of a health literate-sensitive training and conversation aid to support shared decision-making in maternity care - Laxsini Murugesu; Mirjam P. Fransen; Danielle R.M. Timmermans; Arwen H. Pieterse; Ellen M.A. Smets; Olga C. Damman (Elsevier, 2024)
Background: Maternity care increasingly aims to achieve Shared Decision-making (SDM), yet seemingly not to the benefit of clients with low health literacy (HL). We developed an SDM training for healthcare professionals (HCPs) and a conversation aid to support HL-sensitive SDM in maternity care. Methods: The training and conversation aid were based on previous needs assessments and expert consultation, and were developed in co-creation with clients (n = 15) and HCPs (n = 7). Usability, acceptability and comprehension of the conversation aid were tested among new clients (n = 14) and HCPs (n = 6). Acceptability of the training was tested among midwifery students (n = 5). Results: In the co-creation sessions, clients reported to expect that their midwife becomes acquainted with their general values, priorities and daily context. Clients also emphasized wanting to be supported in their preferred decisional role. User test interviews showed that clients and HCPs were positive towards using the conversation aid, but also apprehensive about the time it required. The user test of the training showed that more attention was needed for recognizing and adapting information provision to clients' HL level. Conclusion and innovation: The newly developed conversation aid and training have potential to support HCPs and clients in HL-sensitive SDM.